Efforts to Improve Student Creativity using Problem-based Learning Model at SMAN 2 Kota Batu (Faculty of Social Science, Universitas Negeri Semarang, 2022)
The problem in this study is the lack of learning methodology, namely the optimization of the use of learning media and infrastructure in learning carried out by the teacher so that the learning process is boring. The result is that students' ideas and ideas do not emerge because of the lack of opportunity and freedom given by the teacher. This research was conducted in class XI 8 SMAN 2 Batu involving 34 students. This study used Action Research which was carried out in 2 cycles, namely cycle I and cycle II. This study aims to increase student creativity using the application of the Problem-based Learning model. The data obtained from this study is that there is an increase from pre-action to cycle I and cycle II. This can be seen from the pre-action results data, it is known that students who have a high level of creativity are as many as 27 people (79%), while 7 people (21%) have a low level of creativity. In cycle I, it can be seen that the increase is around 3% and in cycle II it has increased by 5%, namely, 30 people (87%) have a high level of creativity, while 4 people (13%) have a low level of creativity. Thus it can be concluded that the application of the Problem-based Learning model in teaching Pancasila education can increase the creativity of class XI 8 students at SMAN 2 Batu.